Costs and Returns Analysis of Farmers in Mangosteen Community Enterprise Plaeng Yai Khitchakut , Chanthaburi Province. - Karam, Pattama; Tawinruk, Pramote; Saraithong, Atchawan; Uraipan, Naris; Ridsomboon, Jantana (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This research studied the costs and returns of mangosteen farming among 26 farmers in the community enterprise in Khao Khitchakut District, Chanthaburi Province, using in-depth interviews. The study found that farmers who owned their land had net profits of 26,355 baht per rai in 2021, which decreased to 14,901 baht per rai in 2022, with return on investment (ROI) rates of 39.19% and 13.28% respectively, considered unprofitable. Farmers who rented land showed more volatile returns, earning high profits of 85,323 baht per rai in 2021 with a profitable ROI of 126.87%, but suffered net losses of 33,871 baht per rai in 2022 with a negative ROI of -30.18%. The study concluded that 2021 had significantly better yields and returns than 2022 due to unfavorable weather conditions and increased production costs in 2022. Additionally, land rental resulted in more volatile returns compared to land ownership. Article history: Received 21 April 2025 Revised 19 September 2025 Accepted 21 September 2025 SIMILARITY INDEX = 3.51 %